Malignant islet-cell tumour of the pancreas presenting with non-bacterial thrombotic endocarditis and eosinophilia. Issue 669 (July 1981) - O'Boyle, C. P.; Dempsey, J.; Otridge, B.; Barniville, H.
Abstract : A case of severe persistent eosinophilia and non-bacterial thrombotic endocarditis complicating a malignant islet-cell tumour of the pancreas is documented. Although these are well recognized complications of malignant tumours, they do not appear to have been previously documented from the same patient. These complications probably reflect ectopic synthesis and are unlikely to be causally interrelated.